Electrospun PCL/PVA Coaxial Nanofibers with Embedded Titanium Dioxide and Magnetic Nanoparticles for Stabilization and Controlled Release of Dithranol for Therapy of Psoriasis - Natália Andrýsková; Paul Sourivong; Melánia Babincová; Peter Babinec; Mária Šimaljaková (Magnetochemistry, 2023)
Dithranol is one of the oldest and most efficient drugs used in the treatment of psoriasis. One of the challenges with using dithranol is its photostability, because it easily degrades when exposed to light. This study investigated the potential of coaxial core-sheath PCL/PVA nanofibers as a dual-functional system for enhancing dithranol photostability and remote-controlled drug delivery for psoriasis therapy. We have shown that coaxial nanofibers with titanium oxide nanoparticles (reflecting and absorbing ultra-violet light) in the PVA-based sheath part of the nanofibers can increase dithranol photostability. Incorporation of dithranol and magnetic nanoparticles into a PCL-based core of the nanofibers enables dithranol release control via an external radio-frequency field. The application of a radio-frequency field generates heat that can be used to control the release rate of drugs. Our approach therefore offers a non-invasive and remotely controlled drug release system that hold promise for the development of new topical formulations for psoriasis treatment using dithranol.